Distinct effects of calorie restriction on adipose tissue cytokine and angiogenesis profiles in obese and lean mice - Kurki Eveliina (Nutrition & Metabolism, 2012)
Abstract Background Obesity associates with low-grade inflammation and adipose tissue remodeling. Using sensitive high-throughput protein arrays we here investigated adipose tissue cytokine and angiogenesis-related protein profiles from obese and lean mice, and in particular, the influence of calorie restriction (CR). Methods Tissue samples from visceral fat were harvested from obese mice fed with a high-fat diet (60% of energy), lean controls receiving low-fat control diet as well as from obese and lean mice kept under CR (energy intake 70% of ad libitum intake) for 50 days. Protein profiles were analyzed using mouse cytokine and angiogenesis protein array kits. Results In obese and lean mice, CR was associated with 11.3% and 15.6% reductions in body weight, as well as with 4.0% and 4.6% reductions in body fat percentage, respectively. Obesity induced adipose tissue cytokine expressions, the most highly upregulated cytokines being IL-1ra, IL-2, IL-16, MCP-1, MIG, RANTES, C5a, sICAM-1 and TIMP-1. CR increased sICAM-1 and TIMP-1 expression both in obese and lean mice. Overall, CR showed distinct effects on cytokine expressions; in obese mice CR largely decreased but in lean mice increased adipose tissue cytokine expressions. Obesity was also associated with increased expressions of angiogenesis-related proteins, in particular, angiogenin, endoglin, endostatin, endothelin-1, IGFBP-3, leptin, MMP-3, PAI-1, TIMP-4, CXCL16, platelet factor 4, DPPIV and coagulation factor III. CR increased endoglin, endostatin and platelet factor 4 expressions, and decreased IGFBP-3, NOV, MMP-9, CXCL16 and osteopontin expressions both in obese and lean mice. Interestingly, in obese mice, CR decreased leptin and TIMP-4 expressions, whereas in lean mice their expressions were increased. CR decreased MMP-3 and PAI-1 only in obese mice, whereas CR decreased FGF acidic, FGF basic and coagulation factor III, and increased angiogenin and DPPIV expression only in lean mice. Conclusions CR exerts distinct effects on adipocyte cytokine and angiogenesis profiles in obese and lean mice. Our study also underscores the importance of angiogenesis-related proteins and cytokines in adipose tissue remodeling and development of obesity.